Effect of Topical Mometasone Furoate Cream (0.01 % w/w) on Blood Pressure, Blood Sugar and Blood Calcium Level - Chetan Javsen; Avanti Ghadage (Walawalkar International Medical Journal)
Background: Corticosteroids are commonly administered for skin diseases over short durations, typically ranging from a few days to a few weeks. The choice of corticosteroid is based on its potency, which is determined by the application site and the severity of the condition. The adverse effects associated with corticosteroid use are influenced by their strength, the length of the treatment, and the extent of the affected area. Material and Methods: This study examined the impact of topical mometasone furoate on blood pressure, blood sugar, and blood calcium levels after seven days of application. Additionally, the study assessed the relationship between the absorbed concentration of corticosteroids and their effects on blood pressure, blood sugar, blood calcium, and the extent of the body surface area involved. Result: After seven days of mometasone furoate use, no significant changes were observed in blood pressure, blood sugar, or blood calcium levels. The extent of the drugabsorbing surface area was found to be directly proportional to the blood concentration of corticosteroids. The effects on blood pressure, blood sugar, and calcium levels were dependent on the absorbed concentration, which, in turn, was influenced by the drug-absorbing surface area. Conclusion: The application of Mometasone Furoate to skin lesions does not result in significant absorption into the bloodstream at measurable levels and absorb concentration of corticosteroids in the blood increases in proportion to the extent of the area treated with topical steroids. Mometasone Furoate did not cause any changes in either systolic or diastolic blood pressure, blood sugar or calcium levels after seven days.